Changes in shore platform wetting and drying cycles following the 2016 Kaikōura earthquake: Implications for incipient marine terrace evolution. Issue 12 (8th July 2022) - Horton, Sophie L.; Stephenson, Wayne J.; Dickson, Mark E.
Abstract: Co‐seismic uplift of Kaikōura Peninsula in 2016 has substantially reduced the number of wetting and drying cycles that occur on the shore platforms and the newly uplifted incipient marine terraces. A simple empirical model incorporating field and laboratory measurements was used to determine the number and frequency of wetting and drying cycles. The mudstone supratidal terraces are vulnerable to material disintegration and slaking through sustained drying, and occasional sweeping by storm waves. Overall, wetting and drying cycles have decreased on six of eight field transects, between −8% and −148%, resulting in prolonged drying of the supratidal terraces following uplift (upwards of a 29% increase in annual drying hours). We conclude that accelerated rates of denudation due to enhanced drying post‐uplift are likely to return sections of the incipient mudstone terraces to their former intertidal pre‐uplift state, potentially removing evidence of the co‐seismic uplift event. Terrace preservation, however, will likely be highly variable between locations depending on its inherited morphology, lithological vulnerability, and the timing of any future tectonism. Abstract : Increase in shore platform drying hours following co‐seismic uplift.